Etiology of purulent-inflammatory infections in injuries caused by combat operations and sensitivity of pathogens to antimicrobial preparations (Environment & Health, 2024)
The purpose of the study is to investigate the etiological structure of purulent-inflammatory infections in injuries that occurred because of hostilities in Ukraine and to assess the antibiotic resistance of isolated pathogens.Materials and methods: Collection and transportation of samples of biological material from patients with injuries was carried out in accordance with the general principles of selection and transportation. Sowing, selection and identification of isolates was carried out by routine methods using the EUCAST methodology for determining the sensitivity of microorganisms to antimicrobial drugs by the disk diffusion method.Research results and their discussion: During the conduct of 154 microbiological studies of the wound contents of the wounded, 110 isolates were isolated and identified - 97 strains of opportunistic microorganisms and 13 strains of yeast-like fungi. At the same time, 68.2% of cultures were found in monoculture, and 31.8% in associations. To a greater extent, representatives of the gram-positive cocca flora were isolated from the wounded patients - 72.2%: Staphylococci (77.1%), Enterococci (14.3%), Streptococci (8.6%). Among the Staphylococci the following stood out Staphylococcus aureus (72.8%), Staphylococcus haemolyticus (5.9%). Among Enterococci the following stood out Enterococcus faecalis (12.8%), Enterococcus faecium (1.4%). Among Streptococci, Streptococcus pyogenes stood out - 11.8%.To a less extent, gram-negative bacteria were released from the wounded patients - 27.8%: Enterobacteria (70.4%), non-fermenting gram-negative bacteria (29.6%). Among the Enterobacteria the following stood outEsherichia coli (33.3%), Klebsiella pneumoniae (18.5%), Proteus mirabilis 11.1%, Citrobacter freundii (3.7%), Klebsiella oxytoca (3.7%). Among the NFHNB the following stood out Acinetobacter baumanni (14.8%), Pseudomonas aeruginosa (11.1%), Pseudomonas putida (3.7%). Among the yeast-like fungi, Candida albicans was mainly isolated - 76.9%. Candida non-albicans was isolated to a less extent - 23.1%.Conclusions. According to the results of the conducted microbiological research, the etiological structure of purulent-inflammatory infections in victims of hostilities in Ukraine for 2022-2023 was studied.The spectrum of isolated pathogens consists of 72.2% gram-positive and 27.8% gram-negative bacteria. Yeast-like fungi of the genus Candida spp. Isolated from wounds in 11.8%.Conducted studies on the assessment of antimicrobial resistance of selected causative agents of wound infections. Installed high resistance of selected microorganisms to antimicrobial drugs of various chemical groups.
Keywords: bacteria; fungi; purulent-inflammatory infections; victims of hostilities; antimicrobial drugs